Comparative study of cobalt sulphides properties for photocatalytic and battery applications. (27th August 2019) - Hussain, Wajid; Malik, Hinna; Khan, Maroof Ahmad; Iqbal, Muhammad Javed; Hussain, Raja Azadar; Shoukat, Rizwan; Khan, Yaqoot; Badshah, Amin; Sulaman, Muhammad; Li, Hui
Abstract: Transition metal sulphide nanoparticles have evolved into a most significant group of nanomaterials due to their easy synthesis in surface chemistry and physics for various applications. This article describes the synthesis of CoS nanoparticles (NPs) and nanoslabs (NSs) utilizing two different routes viz., a single-source (SS) and multi-source (MS) method, jointly. The photocatalytic activity was well racked up across four cationic organic dyes e.g. methyl violet (MV), methylene blue (MB), malachite green (MG), and rhodamine B (RhB) under direct sunlight. The higher photocatalytic activity was noticed in CoS NPs rather than CoS NSs due to their high band gap and spherical morphologies. Moreover, the kinetic study also reveals a higher rate of constant for MV, MB, MG and RhB degradation by CoS NPs as compared to CoS NSs. Additionally, battery application was evaluated by trying out the electrochemical discharge/charge at voltage limits of 0.0–3.0 V across Li/Li + . The Organic precursors were characterized by 1H and 13C nuclear magnetic resonance, whereas composition, phase pattern, size and morphology were peculiarized by EDS, P-XRD, SEM, and TEM, respectively.